Isotopic niches of diadromous fishes inform on interspecific competition in an obstructed catchment - Lizé, Anne; Teichert, Nils; Roussel, Jean-Marc; Acou, Anthony; Feunteun, Eric; Carpentier, Alexandre (Frontiers in Ecology and Evolution, 2023)
Competition arises when species share a limited resource but can be avoided through niche partitioning. Despite the large body of literature on diadromous fishes, very few studies have focused on niche partitioning when competing for resources. Diadromous fishes are suffering a global decline throughout their range in part due to their peculiar life history traits as they migrate from the sea to freshwater to spawn or the reverse. They are particularly sensitive to river fragmentation induced by barriers. Dams for instance are expected to alter the spatial distribution and resource exploitation of diadromous fishes as well as other organisms. Here, we studied the ecological niche of six taxa of diadromous fishes, temporally co-occurring in the same land-sea continuum obstructed by two river dams. We used Bayesian mixing models run on C and N isotopes to infer the various habitats used and the origin of the trophic carbon in muscle and scale tissues of diadromous. Results showed that the sub-adults of Anguilla anguilla, juveniles of Petromyzon marinus, and Salmo trutta exploit mainly the freshwater, or marine part for adults of Lampetra fluviatilis, whereas juveniles of Platichthys flesus and Mugilidae use all the habitats of the land-sea continuum. In the freshwater habitat, the microphytobenthos and biofilm are the main source of carbon used, while in the marine habitat, the basal carbon sources are more diverse. The analyses of niche overlaps between diadromous, demonstrate that the widest isotopic niches, observed for A. anguilla and P. flesus, are also the more impacting ones within the community. Results are discussed in terms of intra-and 2 This is a provisional file, not the final typeset article inter-competition between these diadromous and their generalist/specialist strategies in an obstructed catchment.